(untitled) (Medical Forum Monthly, 2024)
Objective: The study was carried out to determine the prevalence of pityriasisversicolor and its association with ABO blood groups in out patients’ department of Dermatology at Islam teaching hospital Sialkot. Study Design: Prospective analytical. Place and Duration of Study: This study was carried out the Department of Dermatology, Islam Teaching Hospital, Sialkot; from December 2012 to December. 2015. Materials and Methods: All patients reporting to our OPD during a period of 3 years were included. The patients with mixed infections were excluded and those did not get their blood grouping and less than 3 months treatment & follow up were excluded from the study. All rashes were examined with wood’s lamp. Skin scrapings were taken for KOH examination. Blood samples of all the patients were sent for blood group typing. Data of patients was analyzed using SPSS version 22. Results: Out of 6423 patients attending skin OPD, 197 patients were diagnosed as having Pityriasis versicolor; only 170 patients fulfilled the inclusion criteria. Male to female ratio 71: 29. Most of the patients fell in age group 15-50 years. Commonest rash was in multiple areas while followed by Upper trunk only. The prevalence of pityriasisversicolor was more with blood group B and O. Conclusion: The pattern of distribution of rash is most commonly mixed while upper trunk involvement is next in our patients. The study depicts strong association of Pityriasis Versicolor with blood group B and O.